Influence of distributed leadership on employee innovative behaviour: the mediating role of psychological empowerment - Liao Dongxian; Hira Batool (Journal of Innovation and Entrepreneurship)
Abstract Employee innovative behaviour shapes the core competitiveness of an enterprise. Leadership style has been shown to influence employee innovative behaviour significantly. This research paper fills the gap by exploring the relationship between distributed leadership as an emerging leadership style and employee innovative behaviour along with psychological empowerment as mediator and organizational innovation climate as a moderator. 567 responses were collected from 29 different regions in China based on their availability through an adapted questionnaire. The data were analyzed using statistical software Mplus 6.0 and SPSS 19.0. The research results show that distributed leadership not only positively affects the innovative behaviour of employees but also has a positive impact on psychological empowerment and such empowerment positively influences employee innovative behaviour. The results also confirm that psychological empowerment mediates the relationship between the innovative behaviour of employees and distributed leadership. In addition, the organizational innovation climate moderates the relationship between psychological empowerment and the innovative behaviour of employees. The study not only contributed by confirming the moderating effect of organizational innovation climate on the relationship between psychological empowerment and employee innovative behaviour but also added directions for future researchers to explore more about the relationship between psychological empowerment and employee innovative behaviour along with theoretical research on enterprise leadership and management.